Impact of COVID-19 on mutual fund returns by style / Jacob Ongaki - Ongaki, Jacob (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This quantitative investigation examined the mutual fund performances (1 and 3-year annual returns) by fund size and style (large-cap growth, large-cap blend, and large-cap value) during the COVID-19 pandemic. The study data were obtained from Morningstar 4 and 5-star fund ratings controlling the standard deviation and top-10 holdings of the United States equity MF. The Morningstar 1-year and 3-year annual returns were utilized for the study. The General Linear Model- Multivariate Analysis method was utilized for this investigation. The investigation revealed that the large-cap (growth, blend, and value) fund category produced superior annual returns during the COVID-19 pandemic. The covariate standard deviation impacted the 1- and 3-year annual returns. However, the Top-10 percentage asset holdings had mixed results on the 1-year and 3-year annual returns. The investigation showed performance differences among fund sizes and styles based on the expected utility theory. Investors and asset managers should consider fund style and size to make short-term and long-term financial investment decisions during bear market periods such as the COVID-19 pandemic.